The marketplace of democracy : electoral competition and American politics - McDonald, Michael, 1967-; Samples, John Curtis, 1956- (Cato Institute : Brookings Institution Press, 2006)
Since 1998, U.S. House incumbents have won a staggering 98 percent of their reelection races. Electoral competition is also low and in decline in most state and primary elections. The Marketplace of Democracy combines the resources of two eminent research organizationsthe Brookings Institution and the Cato Instituteto address the startling lack of competition in our democratic system.